Adsorptive Exhaust Gas Cleaning for Recycling of Li-Ion-Batteries. (6th January 2017) - Stehmann, Friederike Maria; Jahnke, Stefan; Balmforth-Slater, Charlotte; Scholl, Stephan
Abstract : Increasing the usage of lithium-ion batteries requires sufficient recycling strategies in order to save resources. In the collaborative research project LithoRecII a recycling process was investigated, that combines the process steps of discharging, dismantling, shredding, extraction, drying and separation. The grinding and drying stages are flushed with an inert drying gas producing an off-gas loaded with different organic solvent components. High boiling components can be easily removed with condensation, while low boiling components require very low condensation temperatures to achieve sufficient cleaning. Hence the final cleaning can be achieved by adsorption. This paper addresses the identification of the main influences on the exhaust gas flow and composition based on drying and condensation parameters as well as the results of adsorptive off-gas cleaning experiments carried out in a fixed-bed adsorber.